Editorial to Special Issue “Multispectral Image Acquisition, Processing and Analysis—2nd Edition” - Benoit Vozel; Vladimir Lukin; Yakoub Bazi (Remote Sensing)
Modern means of remote sensing (RS) in general and multispectral imaging in particular have experienced rapid development in recent years [...]